2021
DOI: 10.1080/02813432.2021.1913904
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine consultations with physicians in Swedish primary care: a mixed methods study of users’ experiences and care patterns

Abstract: Objective: The study aimed to explore users' experiences and care patterns concerning telemedicine consultations with physicians in Swedish primary care from 2017 to 2019. Objective: Design and participants: A mixed methods study involving 26 qualitative interviews with users of telemedicine consultations from a national sample, complemented by a quantitative registry study of data from 10,400 users in a Swedish region. Results: Users mainly described telemedicine consultations as a positive experience and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(91 citation statements)
references
References 34 publications
(63 reference statements)
7
84
0
Order By: Relevance
“…22 Patient acceptance of telemedicine is generally high. [11][12][13][14]23 Physician attitudes and experiences have been more mixed. 11,12,24,25 Important areas for physician acceptance of telemedicine include perceived usefulness and ease of use, technical concerns, effects on workflow, and security issues.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…22 Patient acceptance of telemedicine is generally high. [11][12][13][14]23 Physician attitudes and experiences have been more mixed. 11,12,24,25 Important areas for physician acceptance of telemedicine include perceived usefulness and ease of use, technical concerns, effects on workflow, and security issues.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Telemedicine consultations meet the current health care needs of patients while demonstrating convenience. Patients are usually satisfied with the service and have the ability to choose when to conduct consultations [ 10 ]. Telemonitoring reduces the number of visits and hospital admissions, thus, scarce medical resources can be used effectively [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…All methods aim to allow the transmission of medical information and realize communication between patients and medical workers. But they still have different, telemedicine consultation is defined as patients consulting the specialist via video or chat which is more interactive and human-centered and can be customized to the individual needs of patients [ 9 , 10 ], telediagnosis is one of the most developed components of telemedicine[ 11 ], it makes use of technology to exchange images and data for making a diagnosis of disease[ 12 ] and often does not require direct clinical examinations[ 13 ], tele-mentoring is used in medical education to disseminate the knowledge and technology, such as fall prevention and infection control [ 14 , 15 ], telemonitoring involves remote monitoring using mobile devices or computers to monitor the patients’ vital signs or indicators of disease and is usually used by care providers in different locations[ 16 ]. Applications are used as platforms that allow for patients and providers to communicate [ 7 ] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A Swedish study in a primary care setting found that patients enjoyed the more anonymous character of these consultations, although others preferred face-to-face meetings. An important advantage of this tool is that it allows patients to refer back to what had been said by them and the physician ( 36 ). There is preliminary evidence in favor of self-management in headache medicine ( 37 ) and for other pain conditions such as low back pain ( 38 ).…”
Section: Discussionmentioning
confidence: 99%